Elementos para el análisis de la imagen social de los profesores - Vera Vila, Julio (Teoría de la Educación. Revista Interuniversitaria, 2009)
As a result of the complexity of the educational fact and the fast-changing society, the teaching profession has become a difficult task to carry out. Moreover, scholar institution is being strongly argued, and there is no social recognition of the trouble borne in being a teacher nowadays. By the analysis of these facts, some of the distinctive features of the teacher's social image in the present time are depicted. How that image can become upsetting for the bearing professionals is deduced.